Study on hydrostatic reduction of intussusception under general anaesthesia without ultrasound guidance - San, Diljith; P., Ranjit; Ainipully, Arun M. (International Surgery Journal, 2020)
Background: Currently the recommended treatment for intussusception is ultrasound guided hydrostatic reduction under sedation. The procedure is very safe due to real-time visualisation, but inadequate sedation and absence of muscle relaxation may cause difficulty during the procedure. Muscle relaxation under general anaesthesia will make reduction of mass easier. In this context, we conducted this study of hydrostatic reduction of intussusception under general anaesthesia without USG guidance. Methods: In this prospective study eighty two children were treated for intussusception from January 2010 to December 2010. General anaesthesia was induced and lump was confirmed. Normal saline was infused through Foleys catheter and i.v. drip set into rectum from saline bottle kept 3 feet above operating table. Saline reduction was done, and if not reduced a second attempt was done. Partially reduced or failed cases underwent immediate surgery. In successful cases, reduction was confirmed by ultrasound. Results: Hydrostatic reduction under general anaesthesia was done in 78 children. In 54 patients (68%) procedure was successful with no residual mass in check ultrasonogram. 24 (30.7%) patients required surgical treatment, immediate surgery in 18 and delayed surgery in 6 patients. Procedure was uncomplicated in 77 patients (98.7%). One patient developed peritonitis due to delayed presentation. Conclusions: Hydrostatic reduction is treatment of choice in intussusception unless contraindicated. Hydrostatic reduction under general anaesthesia without ultrasound guidance is safe and effective. Hospital stay is less for hydrostatic reduction. Failure with hydrostatic reduction is more if mass extends distal to splenic flexure. Most failed cases were easily reducible by laparotomy.